Evaluation of consumer properties of grain of spring soft wheat selection lines - T. A. Barkovskaya; O. V. Gladysheva; V. G. Kokoreva (Аграрная наука Евро-Северо-Востока, 2021)
The article presents the results of studying 10 numbers of competitive variety testing in the Ryazan region in order to identify new breeding lines of spring soft wheat with high technological and baking indicators. The assessment carried out in 2017-2019 revealed that according to the yield the breeding lines 1036-09Н21 and 898-09Н125 exceeded the Agata standard variety (4.47 t/ha) by 0.61 t/ha and 0.48 t ha, respectively (LSD05 = 0.34 t/ha). Over the years of the research, the variety samples formed a glassy well-made grain with the nature of 770-817 g/l, with the protein content in the grain of 14.1-16.0 % and the mass fraction of raw gluten in the flour of 29-41 % of high quality (IDK 45-75 units). The greatest potential for protein accumulation in grain was possessed by the varieties Agata, RIMA, lines 539-10H163, 543-13H163 – 16.8-19.3 %. On the average, the falling number was relatively high 264-331 s, corresponding for wheat of the first and second classes. Lines 543-13H163, 539-10H163 and 898-09H125 exceeded the standard in terms of sedimentation value by 15-17 ml or 35-40 %. The specific work of the dough deformation in the samples varied from 305 a.u. up to 421 a.u., corresponding to the standards of strong or valuable wheat. It has been established that the volumetric yield of bread for lines 509-13Н148, 539-10Н163 and 543-13Н163 was 1633-1647 cm3, higher than the Agat standard variety by 16-17 %. Valuable material 539-10N163 and 898-09N125 that meets the requirements of flour-grinding and bakery enterprises has been developed. It has the following varietal characteristics: grain nature is more than 800 g/l, protein content in grain is 15-16 %, gluten in flour is 33-34 %, with the sedimentation indicator of 58-60 ml, the deformation energy of the dough of 389-421 a.u, the volumetric bread yield of 1523-1647 cm3.